A mechanistic investigation exploring the differential transfection efficiencies between the easy-to-transfect SK-BR3 and difficult-to-transfect CT26 cell lines - Elizabeth Figueroa; Pallavi Bugga; Vishwaratn Asthana; Allen L. Chen; J. Stephen Yan; Emily Reiser Evans; Rebekah A. Drezek (Journal of Nanobiotechnology, 2017)
Abstract Background Gold–polyamidoamine (AuPAMAM) has previously been shown to successfully transfect cells with high efficiency. However, we have observed that certain cell types are more amenable to Au–PAMAM transfection than others. Here we utilized two representative cell lines—a “difficult to transfect” CT26 cell line and an “easy to transfect” SK-BR3 cell line—and attempted to determine the underlying mechanism for differential transfection in both cell types. Using a commonly established poly-cationic polymer similar to PAMAM (polyethyleneimine, or PEI), we additionally sought to quantify the relative transfection efficiencies of each vector in CT26 and SK-BR3 cells, in the hopes of elucidating any mechanistic differences that may exist between the two transfection vectors. Results A comparative time course analysis of green fluorescent protein reporter-gene expression and DNA uptake was conducted to quantitatively compare PEI- and AuPAMAM-mediated transfection in CT26 and SK-BR3, while flow cytometry and confocal microscopy were used to determine the contribution of cellular uptake, endosomal escape, and cytoplasmic transport to the overall gene delivery process. Results from the time course analysis and flow cytometry studies revealed that initial complex uptake and cytoplasmic trafficking to the nucleus are likely the two main factors limiting CT26 transfectability. Conclusions The cell type-dependent uptake and intracellular transport mechanisms impacting gene therapy remain largely unexplored and present a major hurdle in the application-specific design and efficiency of gene delivery vectors. This systematic investigation offers insights into the intracellular mechanistic processes that may account for cell-to-cell differences, as well as vector-to-vector differences, in gene transfectability.